Antagonism of toll-like receptor 2 attenuates the formation and progression of abdominal aortic aneurysm - Huimin Yan; Bing Cui; Xiaowei Zhang; Xiaoming Fu; Jun Yan; Xiaoxing Wang; Xiaoxi Lv; Zhong Chen; Zhuowei Hu (Elsevier, 2015)
Abdominal aortic aneurysm (AAA) is an inflammatory vascular disorder with high mortality. Accumulating evidence shows that toll-like receptor 2 (TLR2) plays a critical role in the regulation of wound-repairing process after tissue injury. We wondered if TLR2 signaling contributed to the pathogenesis of AAA and that targeting TLR2 would attenuate AAA development and progression. In this study, enhanced expression of TLR2 and its ligands were observed in human AAA tissue. Neutralization of TLR2 protected against AAA development and caused established AAA to regress in mouse models of AAA. In addition, TLR2-deficient mice also failed to develop AAA. The prophylactic and therapeutic effects of blocking TLR2 were accompanied by a significant resolution of inflammation and vascular remodeling, as indicated by the decreased expression or activity of MMP-2/9, α-SMA, inflammatory cytokines, and transcription factors NF-κB, AP-1 and STAT1/3 in AAA tissue. Mechanistically, blocking TLR2 decreased the expression and interaction of TLR2 and several endogenous ligands, which diminished chronic inflammation and vascular remodeling in the vascular tissue of AAA. Our studies indicate that the interactions between TLR2 and its endogenous ligands contribute to the pathogenesis of AAA and that targeting TLR2 offers great potential toward the development of therapeutic agents against AAA.